Crosslinked Decellularized Porcine Pericardium as a Substrate for Conjunctival Reconstruction. (15th March 2022) - Chen, Fangyuan; Deng, Jingyue; Luo, Lishi; Zhu, Ying; Dong, Yuying; Yang, Yuanting; Zhang, Rijia; Chen, Jian; Zhou, Qing
Abstract : Seeking for suitable conjunctival reconstruction substitutes to overcome the limitations of current substitutes, such as amniotic membrane, is urgent. Decellularized tissues have become a promising strategy for tissue engineering. In this study, we prepared decellularized porcine pericardium (DPP) scaffolds by the phospholipase A2 method and crosslinked them with aspartic acid (Asp) and human endothelial growth factor (hEGF) to enhance biological performance on the DPP, obtaining DPP-Asp-hEGF scaffolds. In vitro DPP showed lower apoptosis, highly desirable, well preservation of extracellular matrix components, and favorable macro-microstructure, which was confirmed by histology, immunofluorescence, electron microscopy, collagen and DNA quantification, and cytotoxicity assay, compared to the native porcine pericardium (NPP). The crosslinked efficacy of the DPP-Asp-hEGF was furtherer verified by in vitro experiments with Fourier transform infrared (FTIR) and X-ray diffraction (XRD). Through animal models of conjunctiva defect model, the DPP-Asp-hEGF revealed a closed, multilayer epithelium with an equal amount of goblet cells and no indication for conjunctival scarring after 28 days, compared to amniotic membrane (AM) groups and sham groups. These results suggested that DPP-Asp-hEGF can offer a good conjunctival reconstructive substitute both in structure and in function.